Power and madness in Hamlet: A Foucauldian evaluation - Asha Moni Ritu; Naeem Imtiaz (Universitas Merdeka Malang, 2023)
For the Western consciousness, madness has always welled up simultaneously at multiple points, forming a constellation that slowly shifts from one form to another, its face perhapshiding an enigmatic truth. Meaning here is always fractured. William Shakespeare is renowned for his capacity to manufacture imagination and a great master of his use of psychological studies in the portrayals of insanity. In general, his artwork shows a keen knowledge of human nature. He has a thorough understanding of the human psyche, personality, and actions. Shakespeare's protagonist Hamlet assimilates madness in the most obstinate wisdom. This wisdom may be thin, but it reigns supreme. It presupposes and requires a perpetual doubling of the consciousness of madness, which disappears beneath the surface of madness, only to reappear again on the other side. The paper is an attempt to explore the mindscape of Prince Hamlet using the theoretical base of Michel Foucault's discourse on madness and the formation of power dichotomy. The paper also envisions a Lacanian regeneration of desire, sexuality, and narrative hegemony.